Rare Presentation of Anterior Cervical Arachnoid Cyst in an Adolescent with Rapidly Progressive Quadriparesis: A Case Report - Mallik, Jeevesh; Kumar, Manoj; Choudhary, Niraj Kumar (Asian Journal of Neurosurgery, 2025)
An arachnoid cyst is mostly congenital CSF-filled space occurring in the brain and spine. In the spine, they are usually found in the posterior aspect. Anterior cervical arachnoid cyst is very uncommon. A 14-year-old adolescent boy presented with rapidly progressive quadriparesis starting with the left lower limb, which is associated with radiating pain and numbness in both upper extremities. There was no sensory deficit, and the bladder and the bowel were normal. The radiological evaluation with contrast-enhanced MRI was suggestive of an anterior cervical intradural arachnoid cyst, for which the patient underwent surgery with wide fenestration and partial removal of the cyst wall, and the cyst wall was sent for histopathological examination. The patient improved postoperatively without any residual deficit. Anterior cervical arachnid cyst is a very rare lesion and should be considered in children and young adults who presented with neck pain or radiculopathy, especially if they are followed by motor weakness.
Keywords: accumulation of CSF; anterior cervical arachnoid cyst; arachnoid cysts; intradural arachnoid cyst; spinal arachnoid cysts